Quantification and qualitative effects of different PEGylations on Poly(butyl cyanoacrylate) nanoparticles - Aslund, Andreas K.O; Sulheim, Einar; Snipstad, Sofie; von Haartman, Eva; Baghirov, Habib; Starr, Nichola J.; Løvmo, Mia Kvåle; Lelú, Sylvie; Scurr, David J.; Catharina, de Lange Davies; Ruth, Schmid; Ýrr, Mørch (American Chemical Society, 2017)
Protein adsorption on nanoparticles (NPs) used in nanomedicine leads to opsonization and activation of the complement system in blood, which substantially reduces the blood circulation time of NPs. The most commonly used method to avoid protein adsorption, is to coat the NPs with polyethylene glycol, so called PEGylation. Although PEGylation is of utmost importance for designing the in vivo behavior of the NP, there is still a considerable lack of methods for characterization and fundamental understanding related to the PEGylation of NPs. In this work we have studied four different poly(butyl cyanoacrylate) (PBCA) NPs , PEGylated with different types of PEG-based non-ionic surfactants–Jeffamine M-2070, Brij L23, Kolliphor HS 15, Pluronic F68–or combinations thereof. We evaluated the PEGylation, both quantitatively by nuclear magnetic resonance (NMR), thermogravimetric analysis (TGA) and time-of-flight secondary ion mass spectrometry (ToF-SIMS), and qualitatively by studying zeta-potential, protein adsorption, diffusion, cellular interactions and blood circulation half-life. We found that NMR and ToF-SIMS are complementary methods, while TGA is less suitable to quantitate PEG on polymeric NPs. It was found that longer PEG increases both blood circulation time and diffusion of NPs in collagen gels.